Short-term dynamic changes in neutralizing antibodies against enterovirus 71 after vaccination - Shenyu Wang; Ji Zeng; Xinpei Zhang; Zhengkai Gan; Jianqiang Fan; Yingping Chen; Zhenzhen Liang; Xiaosong Hu; Gang Zeng; Huakun Lv (Taylor & Francis Group, 2020)
Background Short-term dynamic changes in neutralizing antibodies against EV71 and EV71-IgM after inactivated EV71 vaccine injection are unknown. Methods This study was designed as a randomized, open-label study and was registered at ClinicalTrials.gov (NCT03278132). In total, 120 healthy infants aged 6-35 months were randomized 1:1:1 to provide a second blood sample on day 10, day 20, or day 30 after the first vaccine dose, respectively. Results According to the per-protocol set, a rapid immune response against EV71 was observed 10 days after the first EV71 vaccine dose, with antibody titers ≥1:8 in 89.19% of participants (95% CI: 74.58-96.97%) on day 10, in 80.65% (95% CI: 62.53-92.55%) on day 20, in 66.67% (95% CI: 49.03-81.44%) on day 30, and in 100% (95% CI: 96.52%-.) on day 60. Based on an ELISA, the percentages of participants positive for EV71-IgM on day 0 and day 60 were 1.71% (2 out of 117) and 82.86% (87 out of 105), respectively. Conclusions The EV71 vaccine could be used for contingency vaccination to further control EV71-associated disease outbreaks. Caution should be taken in using the EV71-IgM test for rapid EV71 infection diagnosis after EV71 vaccine administration. Clinical Trial Registration ClinicalTrials.gov NCT03278132